2021
DOI: 10.20338/bjmb.v15i3.232
|View full text |Cite
|
Sign up to set email alerts
|

The role of attainability and external focus of attention on standing long jump performance

Abstract: BACKGROUND: External focus of attention (FOA) promotes enhanced performance and learning in comparison to internal FOA; however, several dimensions associated with external FOA appear to have varying influence on motor skill performance. AIM: The purpose of this study was to investigate whether an attainability aspect of external FOA elicits enhanced standing long jump performance. METHOD: Fifteen healthy males performed standing long jumps in the following conditions: without a visual target (Tno), target pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Findings from this study confirmed earlier work from McNevin et al, [11] as the data showed that horizontal jump distance was systematically increased as attention was directed at spatially greater distances from the mover. Since the aforementioned findings, much research using the SLJ has been conducted exploring the distance effect on motor learning and performance with regard to the external far condition [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Findings from this study confirmed earlier work from McNevin et al, [11] as the data showed that horizontal jump distance was systematically increased as attention was directed at spatially greater distances from the mover. Since the aforementioned findings, much research using the SLJ has been conducted exploring the distance effect on motor learning and performance with regard to the external far condition [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%